2020
DOI: 10.1111/ap.12452
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of the experiences, training, and support needs of school mental health workers regarding student trauma

Abstract: Objective School mental health workers are ideally placed to respond to student trauma based on their mental health expertise and the impact of childhood trauma on learning, classroom behaviour, and school relationships. The current study aimed to explore the experiences, and support and training needs of school mental health workers regarding student trauma. Method Thirteen school mental health workers, including school counsellors and wellbeing staff, participated in semi‐structured interviews and their resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…This study found that participants observed and understood that complex childhood trauma impacted upon children's behavior and learning, congruent with previous research (Davis et al, 2018;Berger, 2019;Berger and Samuel, 2020;Collier et al, 2020;Wall, 2020). In this study, participants' accounts of their experiences touched on how they understood complex childhood trauma as manifesting in both externalizing and internalizing behaviors (Doll, 2019;Splett et al, 2019;Olivier et al, 2020;Miller and Berger, 2021), and they identified that lower academic achievement required differentiation in teaching (Deunk et al, 2018;Smale-Jacobse et al, 2019;Miller and Berger, 2021).…”
Section: Understanding Children's Experiencessupporting
confidence: 87%
See 2 more Smart Citations
“…This study found that participants observed and understood that complex childhood trauma impacted upon children's behavior and learning, congruent with previous research (Davis et al, 2018;Berger, 2019;Berger and Samuel, 2020;Collier et al, 2020;Wall, 2020). In this study, participants' accounts of their experiences touched on how they understood complex childhood trauma as manifesting in both externalizing and internalizing behaviors (Doll, 2019;Splett et al, 2019;Olivier et al, 2020;Miller and Berger, 2021), and they identified that lower academic achievement required differentiation in teaching (Deunk et al, 2018;Smale-Jacobse et al, 2019;Miller and Berger, 2021).…”
Section: Understanding Children's Experiencessupporting
confidence: 87%
“…This study is one of the first to report on teachers' experiences of working in remote schools with children living with the effects of complex childhood trauma. It builds on previous work of Brunzell et al (2018), Howard (2019, Stokes and Brunzell (2019), and Berger and Samuel (2020) but is the first to develop a theory that can be used by universities and education systems as a tentative conceptual foundation for preparing teachers to work with children living with the effects of complex childhood trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although research is growing to show the effectiveness and sustainability of TIP in schools (Berger, 2019), limited research has been conducted to explore the strengths and challenges from the perspective of teachers responding to students who have experienced trauma and with diverse cultural needs (Miller & Berger, 2020). Earlier research with teachers has shown that teachers and mental health school staff require more training and assistance to appropriately respond to and support students who have been exposed to trauma (Alisic, 2012;Berger & Samuel, 2020). This study aimed to extend on this research and to be one of the first known studies to explore the experiences of teachers from schools in Australia who have worked with students from refugee backgrounds and who have been exposed to trauma.…”
Section: Introductionmentioning
confidence: 99%
“…This is evidenced by symptoms among mental health staff of anxiety, avoidance of reminders about a student’s traumatic experiences, irritable behaviour, and intrusive negative thoughts about a student’s traumatic experiences (Bride, 2007). Although there is a lack of literature in the area of school mental health and wellbeing staff and students’ DV exposure, the existing research has found that school mental health staff require more training and support to respond to student issues of mental illness and trauma exposure (Berger & Samuel, 2020; Powers et al., 2014).…”
mentioning
confidence: 99%